Price and carbon emission reduction decisions and revenue-sharing contract considering fairness concerns. (20th July 2018) - Li, Qinqin; Xiao, Tiaojun; Qiu, Yuzhuo
Abstract: The members of a supply chain all want to be treated fairly by their counterparts and they dislike unfair shares in a total pie. A retailer exhibits fairness concerns when his share of total profit is low. Existing research on green supply chain does not care about fairness outcome. This paper studies the price and carbon emission reduction decisions in a two-echelon supply chain with a fairness-neutral manufacturer and a fairness-concerned retailer. The impacts of fairness concerns are examined. We obtain several findings: (i) the retailer is better off exhibiting fairness concerns when the emission reduction cost is high; otherwise, it will suffer a loss; and (ii) when the emission reduction cost is lower, the impact of fairness concerns on the manufacturer's profit is greater; however, the impact of fairness concerns on the retailer's profit is smaller; and (iii) the emission tax charged by the government should be lower so as to induce the manufacturer to reduce carbon emissions when the retailer is more fairness concerned. Moreover, we extend the model to involve variable costs and some managerial insights are generated. Highlights: We incorporate the retailer's fairness concerns into carbon emission reduction game models. We explore cross effect of fairness concerns and carbon emission tax on emission reduction level. Retailer's fairness concerns greatly affect price and emission reduction decisions and profits. Retailer is better off exhibiting fairness concerns when the emission reduction cost is high. Win–win situation emerges under revenue-sharing contract when retailer's revenue share is high.